Numerical and Experimental Analysis of the Response of a SAW Structure with WO3 Layers on Action of Carbon Monoxide - HEJCZYK, Tomasz; URBAŃCZYK†, Marian; PUSTELNY, Tadeusz; JAKUBIK, Wieslaw (Archives of Acoustics, 2015)
The paper presents the results of an analysis of gaseous sensors based on a surface acoustic wave (SAW) by means of the equivalent model theory. The applied theory analyzes the response of the SAW sensor in the steady state affected by carbon monoxide (CO) in air. A thin layer of WO3 has been used as a sensor layer. The acoustical replacing impedance of the sensor layer was used, which takes into account the profile of the concentration of gas molecules in the layer. Thanks to implementing the Ingebrigtsen equation, the authors determined analytical expressions for the relative changes of the velocity of the surface acoustic wave in the steady state. The results of the analysis have shown that there is an optimum thickness of the layer of CO sensor at which the acoustoelectric effect (manifested here as a change in the acoustic wave velocity) is at its highest. The theoretical results were verified and confirmed experimentally.